Alkaline hydrolysis of hexahydro-1, 3, 5-trinitro-1, 3, 5-triazine: M06-2X investigation. (September 2015) - Sviatenko, Liudmyla K.; Gorb, Leonid; Hill, Frances C.; Leszczynska, Danuta; Okovytyy, Sergiy I.; Leszczynski, Jerzy
Graphical abstract: Highlights: RDX hydrolysis reaction was modeled along with simulation of UV–VIS spectra. The initial step of hydrolysis is deprotonation of RDX and nitrite elimination. Reaction proceeds toward cycle cleavage. Stable products are 4-nitro-2, 4-diazabutanal, nitrite, formaldehyde, nitrous oxide. Alkaline hydrolysis of RDX is highly exothermic process. Abstract: Alkaline hydrolysis mechanism of possible environmental contaminant RDX (hexahydro-1, 3, 5-trinitro-1, 3, 5-triazine) was investigated computationally at the PCM(Pauling)/M06-2X/6-311++G(d, p) level of theory. Results obtained show that the initial deprotonation of RDX by hydroxide leads to nitrite elimination and formation of a denitrated cyclohexene intermediate. Further nucleophilic attack by hydroxide onto cyclic CN double bond results in ring opening. It was shown that the presence of hydroxide is crucial for this stage of the reaction. The dominant decomposition pathway leading to a ring-opened intermediate was found to be formation of 4-nitro-2, 4-diazabutanal. Hydrolytic transformation of its byproduct (methylene nitramine) leads to end products such as formaldehyde and nitrous oxide. Computational results are in a good agreement with experimental data on hydrolysis of RDX, suggesting that 4-nitro-2, 4-diazabutanal, nitrite, formaldehyde, and nitrous oxide are main products for early stages of RDX decomposition under alkaline conditions.